2018
DOI: 10.1016/j.ebiom.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Identification of Urinary Biomarkers of Pulmonary Tuberculosis

Abstract: BackgroundTuberculosis (TB) is the leading infectious cause of death worldwide. A major barrier to control of the pandemic is a lack of clinical biomarkers with the ability to distinguish active TB from healthy and sick controls and potential for development into point-of-care diagnostics.MethodsWe conducted a prospective case control study to identify candidate urine-based diagnostic biomarkers of active pulmonary TB (discovery cohort) and obtained a separate blinded “validation” cohort of confirmed cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 45 publications
1
37
0
1
Order By: Relevance
“…Previous work from our and other groups showed elevated levels of urinary DiAcSpm in ATB cases (22,43). Additionally, our study demonstrates that DiAcSpm levels decrease rapidly with effective TB treatment.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 76%
See 2 more Smart Citations
“…Previous work from our and other groups showed elevated levels of urinary DiAcSpm in ATB cases (22,43). Additionally, our study demonstrates that DiAcSpm levels decrease rapidly with effective TB treatment.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 76%
“…These findings, therefore, suggest that the molecular markers are not just measuring pharmacological actions of medication on host metabolism, but more importantly are reporting on disease activity itself. Previous work reported that urinary levels of these 7 molecules were elevated in ATB cases compared with cases of non-TB pulmonary disease with an overall sensitivity and specificity of more than 80% before initiation of treatment ( 22 ). Kynurenine, neopterin, and sialic acid levels have also been previously reported to be increased in various human ATB biofluids ( 28 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, previous reports showed that the urinary levels of sialic acid, the terminal glycan of sLe x structure, discriminate patients with active TB from healthy controls or patients with non-tuberculous pulmonary diseases. 35 Also, the regulation of the gene encoding CMAS, the enzyme that provides the substrate for the addition of sialic acid, specifically changed with infection with Mtb. 36 Thus, modulation of sialylated antigens seems to occur in TB, as described in several pathologies, such as other infectious diseases and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the premise that the urine contains the accumulation of all end-product metabolites of the body, logic dictates that chronic bacterial infection(s) of the CNS should, in principle, result in persistent feedback on the gut via the BGA, communicated via the CSF and blood, leading to dysbiosis and an altered urinary metabolome. In research on infectious diseases, urinary profiling has received much attention, in particular regarding pulmonary tuberculosis (TB) -a disease caused by Mycobacterium tuberculosis (Mtb) -about which several studies have been conducted using urine for the detection of clinically relevant biomarkers (Banday et al, 2011;Bonkat, 2012;Das et al, 2015;Luies and Loots, 2016;Luies et al, 2017;Preez et al, 2017;Isa et al, 2018). The detection of lipoarabinomannan (LAM), for instance, a Mycobacterium-specific liposaccharide from the Mtb cell wall, is an example of the basis of a well-studied commercial ELISA assay that shows promise for its diagnostic use in urine with a reported sensitivity of 74% and specificity of 86.9% in a study performed on 148 confirmed TB patients (Tessema et al, 2001); a sensitivity of 80.3% and specificity of 99% in a study conducted on 132 confirmed TB patients (Boehme et al, 2005); and a sensitivity of 44% and specificity of 89% in a study conducted on 195 TB-positive patients in a high-HIV prevalence setting (Mutetwa et al, 2009).…”
Section: Urine Reflects Dysbiosis Within Bacterial Cns Infection(s)mentioning
confidence: 99%